Anti-hyperglycemic effects of dihydromyricetin in streptozotocin-induced diabetic rats - Maojun Yao; Hui Teng; Qiyan Lv; Huifang Gao; Tengming Guo; Yiwen Lin; Sihai Gao; Meihu Ma; Lei Chen (Food Science and Human Wellness)
Dihydromyricetin (DHM), as a bioactive flavanonol compound, is mainly found in “Tengcha” (Ampelopsis grossedentata) cultivated in south of China. This study aimed to investigate the anti-hyperglycemic and anti-dyslipidemic activities of DHM using type 2 diabetes mellitus (T2D) rats, which was induced by feeding with high fat and fructose diet for 42 days and intraperitoneal administration of streptozocin. Forty-eight freshly-weaned rats were randomly assigned into the negative control (Blank), low dose (100 mg/kg), medium dose (200 mg/kg), high dose (400 mg/kg), and positive (40 mg/kg, met) groups. Fasting blood glucose and body weight were measured at weekly interval. Oral glucose tolerance tests were performed on days 42. The results revealed that DHM possessed significant antihyperglycaemic and antihyperinsulinemic effects. Moreover, after the DHM treatment, p-Akt and p-AMPK expression was upregulated, and glycogen synthase kinase-3β (GSK-3β) expression was downregulated, indicating that the potential anti-diabetic mechanism of DHM might be due to the regulation of the AMPK/Akt/GSK-3β signaling pathway.